A retrospective overview of the Asian Review of Accounting during 1992–2019. Issue 3 (30th May 2020) - Kumar, Satish; Sureka, Riya; Pandey, Nitesh
Abstract : Purpose: Asian Review of Accounting (ARA), a leading journal in the field of accounting, completed its 29 years of active publishing in the year 2019. The primary objective of this study is to provide a comprehensive overview of the journal's publishing activities over these years. Design/methodology/approach: The authors use the bibliometric analysis and graphical visualization of bibliographic data to ascertain the publication pattern of ARA. Annual publication and citation structure, leading trends in authorship, institutional affiliation, country affiliation, most cited papers in ARA, documents most cited by ARA and frequency of keyword occurrence are also studied to provide a comprehensive overview of the journal between 1992 and 2019. Findings: Major findings show that ARA has a progressive trend, in terms of both productivity and stature. The journal is highly influenced by Australia and Malaysia in respect of productivity. Major themes published include auditing, financial accounting, governmental and nonprofit accounting, corporate social responsibility, accounting education and financial reporting. Originality/value: This study offers the first of its kind comprehensive summary of the research work published in ARA.